2001
DOI: 10.1351/pac200173101589
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new opportunities with sum-frequency nonlinear optical spectroscopy

Abstract: Over the last decade, infrared-visible sum-frequency generation has been developed into a powerful vibrational spectroscopic technique, especially for surface studies. We give here a brief review of the technique and a few recent applications of the technique to liquid and polymer surfaces. We also describe how the technique has found unique applications in our studies of surface melting of ice, ferroelectric ice films, and molecular chirality in chiral liquids. Doubly resonant sum-frequency generation as surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 15 publications
0
38
0
1
Order By: Relevance
“…Details of the laser system and optical setup used in this study can be found elsewhere. 13,30,31 2.3. Reaction Cell for in Situ Total Internal Reflection-SFG Vibrational Spectroscopy.…”
Section: Ethylene Adsorption On Pt(100) Under Ultrahighmentioning
confidence: 99%
“…Details of the laser system and optical setup used in this study can be found elsewhere. 13,30,31 2.3. Reaction Cell for in Situ Total Internal Reflection-SFG Vibrational Spectroscopy.…”
Section: Ethylene Adsorption On Pt(100) Under Ultrahighmentioning
confidence: 99%
“…SHG experiments are also extensively used to probe interfacial properties when a chromophore is present that can be excited by the visible light. [173][174][175][176] E1(t -τ1) e k 1 ‚r E1(t -τ2) e ik 1 ‚r ks ) 2k1 E1(t -τ1) e k 1 ‚r E2(t -τ2) e ik 2 ‚r ks ) k1 + k2 E 1 * (t -τ1) e -ik 1 ‚r E1(t -τ2) e ik 1 ‚r ks ) 0 E 1 * (t -τ1) e -ik 1 ‚r E2(t -τ2) e ik 2 ‚r ks ) -k1 + k2 E2(t -τ1) e ik 2 ‚r E1(t -τ2) e ik 1 ‚r ks ) k1 + k2 E2(t -τ1) e ik 2 ‚r E2(t -τ2) e ik 2 ‚r ks ) 2k2 E 2 * (t -τ1) e -ik 2 ‚r E1(t -τ2) e ik 1 ‚r ks ) k1 -k2 E 2 * (t -τ1) e -ik 2 ‚r E2(t -τ2) e ik 2 ‚r ks ) 0 E1(t -τ1) e k 1 ‚r E 1 * (t -τ2) e -ik 1 ‚r ks ) 0 E1(t -τ1) e k 1 ‚r E 2 * (t -τ2) e -ik 2 ‚r ks ) k1 -k2 E 1 * (t -τ1) e -ik 1 ‚r E 1 * (t -τ2) e -ik 1 ‚r ks ) -2k1 E 1 * (t -τ1) e -ik 1 ‚r E 2 * (t -τ2) e -ik 2 ‚r ks ) -k1 -k2 E2(t -τ1) e ik 2 ‚r E 1 * (t -τ2) e -ik 1‚ r ks ) -k1 + k2 E2(t -τ1) e ik 2 ‚r E 2 * (t -τ2) e -ik 2 ‚r ks ) 0 E 2 * (t -τ1) e -ik 2 ‚r E 1 * (t -τ2) e -ik 1 ‚r ks ) -k1 -k2 E 2 * (t -τ1) e -ik 2 ‚r E 2 * (t -τ2) e -ik 2 ‚r ks ) -2k2 E(r, t -τ 1 ) ) E 1 (t -τ 1 ) e ik 1 ·r + E 1 * (t -τ 1 ) e -ik 1 ·r + E 2 (t -τ 1 ) e ik 2 ·r + E 2 * (t -τ 1 ) e -ik 2 ·r (57) E(r, t -τ 2 ) ) E 1 (t -τ 2 ) e ik 1 ·r + E 1 * (t -τ 2 ) e -ik 1 ·r + E 2 (t -τ 2 ) e ik 2 ·r + E 2 * (t -τ 2 ) e -ik 2 ·r (58) …”
Section: Appendix A: Possible Second-order Nonlinear Processesunclassified
“…The first SFG paper was published in 1987, examining the adsorption of methanol and pentadecanoic acid monolayers on the glass and water [10]. After that, tremendous progress has been made in the development of SFG theoretical description, instrumentation, data analysis, and applications [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Nowadays SFG becomes a widely used technique by a large number of research groups to study polymer surfaces and interfaces, catalysis, biochemical processes, self-assembled monolayers, and small molecular liquids, ionic liquids, water structures on surfaces and at interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances of SFG studies on the molecular structures of polymer surfaces and interfaces are presented. For more detailed understanding, readers are strongly recommended to look into many SFG review articles [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%